Understanding consumers' dynamic sensory perception for bacon smoked with different Brazilian woods - Saldaña E. (2019)
The authors are grateful to the São Paulo Research Foundation (FAPESP) for funding the project No 2016/15012-2. Soletti I., Marinho M., Schmidt B., Merlo T., are thankful to “Coordenação de Aperfeiçoamento de Pessoal de Nível Superior” (CAPES) for the scholarships. E. Saldaña received the support from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC” from Peru (CIENCIACTIVA programme, PhD scholarship contract agreement No. 104-2016-FONDECYT).